Trends in contraception use in Spanish adolescents and young adults (15 to 24 years) between 2002 and 2008. (June 2013) - Dueñas, José Luis; Lete, Iñaki; Arbat, Agnès; Bermejo, Rafael; Coll, Carme; Doval, José Luis; Martínez-Salmeán, Javier; Pérez-Campos, Ezequiel; Serrano, Isabel
ABSTRACT Objective To assess changes in the use of contraceptive methods, and induced abortion rates, in Spanish adolescents and young adults aged 15 to 24 years, between 2002 and 2008. Study design Representative samples of Spanish men and women aged 15 to 24 years were surveyed in 2002 (N = 1826) and 2008 (N = 2000). Results The rate of use of contraceptive methods increased from 61% in men and 60% in women in 2002 to 80% and 75%, respectively, in 2008. The most commonly used method was the condom (51% in 2002 and 71% in 2008), followed by the contraceptive pill (18% in 2002 and 18% in 2008). None of the adolescents and young adults surveyed used natural methods or the diaphragm, or had undergone sterilisation. The induced abortion rate increased from 9.28 to 13.48 per 1000 women in the group aged between 15 and 19 years, and from 14.37 to 21.05 per 1000 women in the group aged 20 to 24 years. Conclusion Despite an increase in the use of effective birth control methods, the rates of abortion rose during the study period, which may indicate that compliance with the use of condoms is inadequate. There is an urgent need to develop educational campaigns or to design specific policies addressing contraception-related issues for young people.